Establishment the strategy of the food retail companies - Hegedűs, László (Acta Agraria Debreceniensis, 2010)
In this article I have reviewed the SWOT analysis of the two company-group, such as the Hungarian SME and the multinational company. In this frame we have got ready the so called cross-table of the two company-group. These cross-tables have showed, which opportunities they can exploit on the base of their strengths, and which threats will be intensified by their weaknesses. On the base of these results we have found out, that the SME’s realize defensive strategy, while the multinational companies realize outbreaking strategy.